Dust Control Hood For Bag-Filling Machines - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Reduce worker exposure to respirable dust without interfering with bag-filling operations. Approach A dust control hood was developed which contains and captures dust close to its source and prevents it from entering the bag-filling operator's work place. How It Works A sheet metal hood is placed around the nozzle of the bag filling machine. The hood is connected through ducts to the plant exhaust ventilation system. Air pulled into the front of the hood and around the sides of the bag picks up dust generated inside the hood, and carries it to the dust collector. The size of the hood can be adapted to fit most fluidized valve-type bag-filling machines. The height of the hood depends on the bulk density of the product and weight of the bags being filled. The 14-inch-width of the hood allows it to be used on multi-nozzle baging machines spaced 16 inches on center. Only 2/3 of the bag is actually within the hood, and this allows easy operator access for placing the bags on the nozzle.